Infliximab improves vascular stiffness in patients with rheumatoid arthritis. Issue 8 (17th October 2008) - Wong, M; Oakley, S P; Young, L; Jiang, B Y; Wierzbicki, A; Panayi, G; Chowienczyk, P; Kirkham, B
Abstract : Objectives: Patients with rheumatoid arthritis (RA) have increased cardiovascular mortality. Tumour necrosis factor α (TNFα)-blocking therapy has been shown to reduce RA disease activity measures and joint damage progression. Some observational studies suggest that TNFα blockade reduces mortality and incidence of first cardiovascular events. The mechanisms contributing to these outcomes are unclear. This study assessed the effects of infliximab treatment on vascular stiffness and structure in patients with RA. Methods: A post hoc analysis of longitudinal data from a randomised placebo controlled study evaluated the effect of infliximab on vascular assessments. 26 patients received intravenous infliximab (3 mg/kg) at weeks 0, 2, 6 and every 8 weeks thereafter to week 54. Patients were followed up to 56 weeks of infliximab therapy with assessments of RA disease activity, cardiovascular risk factors, vascular stiffness (pulse wave velocity (PWV)), carotid intima media thickness (CIMT) and carotid artery plaque (CAP). Univariate analyses of changes over time by repeated measures analysis of variance (ANOVA) were followed by multivariate time-series regression analysis (TSRA) if changes were seen. Results: PWV was significantly lower (better) after 56 weeks of treatment with infliximab (ANOVA p<0.01, TSRA p<0.01). However, CIMT (ANOVA p = 0.50) and CAP (χ 2 = 4.13, p = 0.88) did not change over the study period. Multiple cardiovascular risk measures did not change with treatment and did not correlate with changes in measures of vascular structure. Conclusions: Arterial stiffness improves with infliximab treatment in RA. This change may help explain the improved cardiovascular disease survival in patients with RA receiving TNFα-blocking therapy.